Influence of donor demographics on the platelet yield during plateletpheresis - experience of 1100 procedures at a tertiary-care hospital - S Mangwana (Association of Clinical Pathologists of Nepal, 2014)
Background: Transfusion of plateletpheresis is effective for treating patients with platelet relatedinsufficiencies while limiting recipient’sexposure to platelets from multiple donors. A larger yield isobtained when donor has a greater number of initial platelets and separation done in a shorter time. Theaim of the study was to analyze the effect of various donors and procedure related parameters on the yieldof single donor platelet so that blood donors can be screened effectively in less time. Materials and Methods: One thousand and one hundred plateletpheresis procedures were performed ina tertiary-care super-specialty hospital onFenwal AMICUS machine using closed system kits. Statisticalanalysis was done to establish cause and effect relationship and to find the extent of relationship betweendifferent variables. Results: Height, weight,BMI, platelet count and total leucocyte count had significant correlation withplatelet yield, processing time and blood volume processed while haemoglobin especially in femalescorrelated significantlywith processing time(p<0.0001)and blood volume processed. Rh “negative”donors had shorter processing time than Rh “positive” donors while ABO group did not show anycorrelation with machine variables. Conclusion: Platelet yield correlated positively with pre-donation count, height, weight and BMI.Haemoglobin correlated with processing time and blood volume processed. Optimization of platelet yieldis an emerging issue to identify factors which may help in selecting donors to obtain higher platelet yieldsin shorter time and consequently better clinical outcome. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10292 Journal of Pathology of Nepal (2014) Vol. 4, 525-529